Pension reform and return-to-work policies. (26th December 2018) - Fitzpatrick, Maria D.
Abstract: For many people, working after beginning retirement benefit collection is a way to enhance financial security by increasing income. Existing research has shown that retirees are sensitive to the Social Security earnings test, which restricts the amount of earnings some beneficiaries can receive. However, little is known about the effects of other types of policies on post-retirement employment. Instead of restricting earnings, many public pension plans restrict the number of hours beneficiaries can work. I use return-to-work rules limiting the number of hours of employment in a state's public pension plan and administrative data on employment and retirement to determine the rules' effects on retirement decisions and post-retirement labor supply. I find that the increases in the maximum number of hours of post-retirement employment lead to no change in retirement benefit collection and to increases in part-time work among retirees. As such, these policies appear to be binding on the labor supply decisions of some employees. These results are relevant for designing policies aimed at extending work-lives or improving the health of pension systems.